Kemampuan Membaca Memahami Teks Bahasa Jerman - Sumiati Sumiati; Abdul Kasim Achmad (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research was conducted at SMA Negeri 3 data and information about Makassar's reading ability. The purpose of this study was to gain an understanding of the German text of class XI students of SMA Negeri 3 Makassar. The subjects of this study were students of class XI IPS, totaling 30 students. The data obtained were then analyzed using the percentage technique. The results of this study indicate that the ability to read German texts in class XI SMA Negeri 3 Makassar is in the good category with a percentage level of 78%.Keywords: Reading Comprehension, Text, German